2018
DOI: 10.1111/tbed.12789
|View full text |Cite
|
Sign up to set email alerts
|

Enterohaemorrhagic and other Shiga toxin-producingEscherichia coli(STEC): Where are we now regarding diagnostics and control strategies?

Abstract: Escherichia coli comprises a highly diverse group of Gram-negative bacteria and is a common member of the intestinal microflora of humans and animals. Generally, such colonization is asymptomatic; however, some E. coli strains have evolved to become pathogenic and thus cause clinical disease in susceptible hosts. One pathotype, the Shiga toxigenic E. coli (STEC) comprising strains expressing a Shiga-like toxin is an important foodborne pathogen. A subset of STEC are the enterohaemorrhagic E. coli (EHEC), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(44 citation statements)
references
References 174 publications
(259 reference statements)
1
40
0
3
Order By: Relevance
“…In a study conducted by [21] in Edo State, Nigeria, a low prevalence of 2.7% was obtained from diarrhoeic patients. In Zahedan, Islamic Republic of Iran, [22] reported that out of 322 stool samples examined from children with diarrhoea, 21 colonies of sorbitol negative E. coli strains (6.5%) were isolated. Serotyping revealed 4 strains positive for E. coli O157: H7, out of which only 2 (0.6%) strains showed positive reaction with anti-H7 and were identified as E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by [21] in Edo State, Nigeria, a low prevalence of 2.7% was obtained from diarrhoeic patients. In Zahedan, Islamic Republic of Iran, [22] reported that out of 322 stool samples examined from children with diarrhoea, 21 colonies of sorbitol negative E. coli strains (6.5%) were isolated. Serotyping revealed 4 strains positive for E. coli O157: H7, out of which only 2 (0.6%) strains showed positive reaction with anti-H7 and were identified as E. coli O157:H7.…”
Section: Discussionmentioning
confidence: 99%
“…Se han descrito casos de portadores humanos sanos 7 . La ECEH resiste bastante bien las condiciones del medio ambiente natural -crece en forma óptima entre los 30 y 42°C-, tolerando incluso temperaturas de congelación y el pH ácido del estómago, pero se inac-tiva y destruye con temperaturas mayores a 68°C 8,9 . Su supervivencia alcanza hasta los 60 días en materia fecal y algunas cepas hasta 104 días en un medio acuático 10 .…”
Section: El Agenteunclassified
“…Es necesario un buen lavado de manos con agua y jabón posterior a tocar animales u otras superficies cercanas a ellos, o antes de ingerir alimentos o líquidos en esos lugares. Se debiese realizar una adecuada limpieza de ropas y especialmente calzado posterior a estas visitas 6,8 . • Transmisión persona a persona.…”
Section: Prevención Primaria ¿Cómo Evitamos La Infección Por Eceh?unclassified
See 1 more Smart Citation
“…Consequently, risk reduction, primarily through consumer education and domestic hygiene training, remains of uttermost importance. Newell and La Ragione () describe current and future diagnostics and control strategies for Shiga toxigenic Escherichia coli (STEC). They argue that a substantial reduction in the public health burden due to this infection will require a multipronged approach, including ongoing surveillance with high‐resolution diagnostic techniques, integrated into routine investigations conducted by public health laboratories.…”
Section: Editorialmentioning
confidence: 99%